Evaluation of Noise Exposure Secondary to Wind Noise in Cyclists. (November 2017) - Seidman, Michael D.; Wertz, Anna G.; Smith, Matthew M.; Jacob, Steve; Ahsan, Syed F.
Objective: Determine if the noise levels of wind exposure experienced by cyclists reach levels that could contribute to noise-induced hearing loss. Study Design: Industrial lab research. Setting: Industrial wind tunnel. Subjects and Methods: A commercial-grade electric wind tunnel was used to simulate different speeds encountered by a cyclist. A single cyclist was used during the simulation for audiometric measurements. Microphones attached near the ears of the cyclist were used to measure the sound (dB sound pressure level) experienced by the cyclist. Loudness levels were measured with the head positioned at 15-degree increments from 0 degrees to 180 degrees relative to the oncoming wind at different speeds (10-60 mph). Results: Wind noise ranged from 84.9 dB at 10 mph and increased proportionally with speed to a maximum of 120.3 dB at 60 mph. The maximum of 120.3 dB was measured at the downwind ear when the ear was 90 degrees away from the wind. Conclusions: Wind noise experienced by a cyclist is proportional to the speed and the directionality of the wind current. Turbulent air flow patterns are observed that contribute to increased sound exposure in the downwind ear. Consideration of ear deflection equipment without compromising sound awareness for cyclists during prolonged rides is advised to avoid potential noise trauma. Future research is warranted and can include long-term studies including dosimetry measures of the sound and yearly pre- and postexposure audiograms of cyclists to detect if any hearing loss occurs with long-term cycling.